2017
DOI: 10.1038/s41598-017-01536-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying disease-associated pathways in one-phenotype data based on reversal gene expression orderings

Abstract: Due to the invasiveness nature of tissue biopsy, it is common that investigators cannot collect sufficient normal controls for comparison with diseased samples. We developed a pathway enrichment tool, DRFunc, to detect significantly disease-disrupted pathways by incorporating normal controls from other experiments. The method was validated using both microarray and RNA-seq expression data for different cancers. The high concordant differentially ranked (DR) gene pairs were identified between cases and controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Many studies have investigated disease-gene and disease-pathway associations with the objective of improving diagnoses [6,7,8,9]. For instance, Zhao et al [8] propose a ranking of disease genes based on gene expression and protein interactions using Katz-centrality.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated disease-gene and disease-pathway associations with the objective of improving diagnoses [6,7,8,9]. For instance, Zhao et al [8] propose a ranking of disease genes based on gene expression and protein interactions using Katz-centrality.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, for a DEG detected at the population-level, we cannot know whether it is differentially expressed in a particular cancer sample because of the heterogeneity of cancer. The REOs analysis method could also be applied to the identification of disease-associated genes or pathways based on one-phenotype disease data when the normal tissues are unavailable or insufficient for some vital organs such like brain and heart [1,[21][22][23]. In this situation, it is of great value to reuse the normal control data accumulated in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, it is of great value to reuse the normal control data accumulated in other studies. And we have proposed a REO-based algorithm, named DRFunc [23], to identify disease-associated pathways based on one-phenotype data through comparing the stable REO in the one-phenotype disease samples with the normal stable REOs background pre-determined in previously accumulated normal samples from other studies. Based on the REOs analysis, we have also proposed a method named "RankCompV2" for identifying DEGs at the population-level through comparing the stable REOs of two phenotypes [24].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, for a DEG detected at the population-level, we cannot know whether it is differentially expressed in a particular cancer sample because of the heterogeneity of cancer. The REOs analysis method could also be applied to the identification of disease-associated genes or pathways based on one-phenotype disease data when the normal tissues are unavailable or insufficient for some vital organs such like brain and heart [1,[17][18][19]. In this situation, it is of great value to reuse the normal control data accumulated in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, it is of great value to reuse the normal control data accumulated in other studies. And we have proposed a REObased algorithm, named DRFunc [19] [21,22]. Several studies have also reported that cigarette smoking [23] and race [24] could alert the gene expression levels, and the gene expression levels change with age in many organ tissues, including lung tissues [25].…”
Section: Introductionmentioning
confidence: 99%